The Effect of Kaolin Addition as a Binder in Making Pellets Iron Concentrate - Septiansyah, Sy.Indra; Afandi, Idris Herkan; Herman, Herman (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
Pellets iron concentrate are formed from fine particles in the form of iron ore concentrate or iron sand after the ore has undergone the agglomeration stage and taken the shape of tiny, marble-like lumps. Iron pellets are also an important raw element in the steelmaking process. The physical, chemical, and metallurgical standards for iron pellet quality vary depending on the specific processing method used to create the pellets. The purpose of this research is to make iron pellets using iron sand derived from zircon sand processing byproducts by adding binders. There are three primary phases in the production of iron pellets, Mixing of iron pellet materials, the second balling process and the third induration process. Materials needed to make iron pellets include water, binder, and iron ore/sand. Typically, bentonite, limestone, and/or similar compounds are used as binder. However, in this study kaolin was used as a substitute for commercial binders with variations of (5; 10; 15 and 20%) binder. Based on the test results kaolin greatly affects the hardness of iron pellets. This can be seen from the results of the Compression Strength Test an average of 107.8 to 156.9 N/Pellet or the equivalent of 11 to 16 Kg/Pellet and the results of the drop test pellets broke at a height of 3 - 4 meters. This indicates that the pellets contain good qualities and exhibit resistance to impacts or mechanical pressure that may arise during transportation or utilization.